anonymous
  • anonymous
find the solution of this system of equation. -3x-7y=-66 and -10x-7y=-24
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
LynFran
  • LynFran
\[-3x-7y=-66\]\[-10x-7y=-24\]by elimination method, take eq2 fram eq1
LynFran
  • LynFran
\[7x=-42\]
LynFran
  • LynFran
solve for x

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
\[A = \left[\begin{matrix}-3 & -7 \\ -10 & -7\end{matrix}\right]\] \[B = \left(\begin{matrix}x \\ y\end{matrix}\right)\] \[C = \left(\begin{matrix}-66 \\ -24\end{matrix}\right)\] \[A ^{-1}C = B\]
LynFran
  • LynFran
x=-42/7
anonymous
  • anonymous
Find the inverse of matrix A and multiply it with C and you get your answer.
LynFran
  • LynFran
then sub x=?? into the 1st eq. to find for y
LynFran
  • LynFran
what did u get for x @Eadorno
anonymous
  • anonymous
I got x=6 is that correct @LynFran
LynFran
  • LynFran
it shd be -6
LynFran
  • LynFran
x=-42/7 x=-6
anonymous
  • anonymous
\[|A| = (-3*-7)-(-7*-10)\]\[A ^{-1} = \frac{ 1 }{ |A| }\left[\begin{matrix}-3 & -7 \\ -10 & -7\end{matrix}\right] = \left[\begin{matrix}\frac{ 1 }{ 7 } & \frac{ -1 }{ 7 } \\ \frac{ -10 }{ 49 } & \frac{ 3 }{ 49 }\end{matrix}\right]\] \[A ^{-1}C = \left[\begin{matrix}\frac{ 1 }{ 7 } & \frac{ -1 }{ 7 } \\ \frac{ -10 }{ 49 } & \frac{ 3 }{ 49 }\end{matrix}\right]\left(\begin{matrix}-66 \\ -24\end{matrix}\right) = \left(\begin{matrix}-6 \\ 12\end{matrix}\right)\]
LynFran
  • LynFran
to find y -3(-6)-7y=-66 18-7y=-66 18+66=7y 84=7y 84/7=y 12=y i like your matrix method too @saseal
anonymous
  • anonymous
nice thank you both @saseal @LynFran
LynFran
  • LynFran
welcome
anonymous
  • anonymous
welcome
anonymous
  • anonymous
@LynFran It's my favorite method so far, works every time.

Looking for something else?

Not the answer you are looking for? Search for more explanations.